STRATEGI PENGEMBANGAN EKOWISATA DI KABUPATEN KEPULAUAN YAPEN PROVINSI PAPUA - Karsudi .; Rinekso Soekmadi; Hariadi Kartodihardjo (Media Konservasi, 2010)
The Regency of Yapen Islands is very potential and feasible to develop as a tourism attraction object. However, the present ecotourism management has not run optimally because of several constraints such as institutional capacity of ecotourism management, attraction management, spatial planning of tourism, promotion and marketing as well as regional security. On the basis of such objective conditions, this research was conducted to formulate strategies for the development of Yapen Islands ecotourism in Papua Province. The results showed that most tourism attractions of the sea, waters and land in the Regency of Yapen Islands are feasible for further development into ecotourism attractions. Some potential tourism objects are not yet possible to develop into ecotourism attractions due to some barriers and constraints, for example (1) unsupportive market potential, (2) objects located at a long distance and difficult to access, (3) below-standard management and services, (4) poor accommodation and (4) quite high relationships with other similar objects. With these objective conditions, the applicable strategy in the tourism development is at present the pessimistic strategy with the following efforts: (1) arrangement of tourism space, (2) development of attraction management (3) development of promotion and marketing, (4) development of regulations and management in ecotourism organization, and (5) creation of a conducive and secure situation both within and outside the tourist area. Keywords :  ecotourism, strategy, Yapen Islands